Multifunctional Graphene–Concrete Composites: Performance and Mechanisms - Jun Shang; Mingyang Wang; Pei Wang; Mengyao Yang; Dingyang Zhang; Xuelei Cheng; Yifan Wu; Wangze Du (Applied Sciences)
Concrete is a cornerstone material in the construction industry owing to its versatile performance; however, its inherent brittleness, low tensile strength, and poor permeability resistance limit its broader application. Graphene, with its exceptional thermal conductivity, stable lattice structure, and high specific surface area, presents a transformative solution to these challenges. Despite its promise, comprehensive studies on the multifunctional properties and underlying mechanisms of graphene-enhanced concrete remain scarce. In this study, we developed a novel concrete composite incorporating cement, coarse sand, crushed stone, water, and graphene, systematically investigating the effects of the graphene dosage and curing duration on its performance. Our results demonstrate that graphene incorporation markedly improves the material’s density, brittleness, thermal conductivity, and permeability resistance. Notably, a comprehensive analysis of scanning electron microscopy (SEM) images and thermogravimetric (TG) data demonstrates that graphene-modified concrete exhibits a denser microstructure and the enhanced formation of hydration products compared to conventional concrete. In addition, the graphene-reinforced concrete exhibited a 44% increase in compressive strength, a 0.7% enhancement in the photothermal absorption capacity, a 0.4% decrease in maximum heat release, a 0.8% increase in heat-storage capacity, and a 200% reduction in the maximum penetration depth. These findings underscore the significant potential of graphene-reinforced concrete for advanced construction applications, offering superior mechanical strength, thermal regulation, and durability.